The Role of Leader Psychological Support in Enhancing Technical Skill Transfer: Examining the Mediating Effect of Task Motivation - Mohamad, Nur Izzaty; Othman , Abdullah Sanusi; Hasan, Haslin; Ab Rashid, Faridah Hanem; Nowalid, Wan Aishah Wan Mohd (International Review of Management and Marketing, 2026)
This study investigates the relationship between leader psychological support, task motivation, and technical skill transfer using a mediation model grounded in empirical research. A quantitative research design was employed, with data collected through a self-administered questionnaire distributed to 210 workforce in the Malaysian education ecosystem. The hypotheses were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM), which allowed for the evaluation of both measurement and structural models. The results revealed that leader psychological support and task motivation significantly and positively influence technical skill transfer, underscoring the pivotal role of leader psychological support in fostering task motivation and, consequently, enhancing technical skill transfer. These findings highlight the importance of organizational strategies that strengthen leader psychological support as a means of cultivating a motivated workforce capable of effectively applying newly acquired skills. In addition, the study offers valuable insights for practitioners by providing a framework to better understand the interplay between leader psychological support and task motivation in driving successful technical skill transfer.